2005
DOI: 10.1021/jp054174k
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Interface and Metal Film Morphology in the Vapor Deposition of Ti on Hexadecanethiolate Hydrocarbon Monolayers on Au

Abstract: The combination of in situ X-ray photoelectron spectroscopy, infrared reflection spectroscopy, atomic force microscopy, and time-of-flight secondary ion mass spectrometry are used to probe the nature of the evolving interface chemistry and metal morphology arising from Ti vapor deposition onto the surface of a CH(3)(CH(2))(15)S/Au{111} self-assembled monolayer (SAM) at ambient temperature. The results show that for a deposition rate of approximately 0.15 Ti atom.nm(-2).s(-1) a highly nonuniform Ti overlayer is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 53 publications
(115 reference statements)
3
43
1
Order By: Relevance
“…37,38 In these systems, however, film growth results from metal atom adsorption and condensation onto cool (25 • C) substrates. Hence, absolute sticking probabilities onto SAMs may be calculated by assuming the sticking of evaporants is unity onto the bare metal.…”
Section: E Parallel Mass Measurement For Relative Sticking Probabilimentioning
confidence: 99%
“…37,38 In these systems, however, film growth results from metal atom adsorption and condensation onto cool (25 • C) substrates. Hence, absolute sticking probabilities onto SAMs may be calculated by assuming the sticking of evaporants is unity onto the bare metal.…”
Section: E Parallel Mass Measurement For Relative Sticking Probabilimentioning
confidence: 99%
“…Ti Clustering on PANI and TiO 2 Substrates. Recent investigations on the initial stage of interface formation in vapor deposition of Ti on various self-assembled monolayers [19][20][21][22] and on nitrogen and halogen containing polymer surfaces 23 have shown that a large fraction of incident Ti atoms do not stick to these organic substrates at room temperature but form isolated clusters, indiscriminatingly reacting with the substrates. Isolated Ti clusters may also form on PANI, which may be the reason for the small number of D 2 molecules adsorbed per Ti.…”
Section: Resultsmentioning
confidence: 99%
“…The Ti2p presents three peaks at 458.4, 456.4 and 454.3 eV, and another are at 464.4, 462.4 and 460.2 eV correspondingly to the Ti2p 3/2 and Ti2p 1/2 . The peaks at 458.4 and 464.4 eV correspond to Ti 4+ in TiO 2 , at 456.4 and 462.4 eV correspond to TiC, but the peaks may be also identified at 462.4 eV because of Ti 4+ 2p 3/2 from TiO 2 , again another remaining one peak at 454.3 and 460.2 eV correspond to TiB 2 (Fig. a) .…”
Section: Methodsmentioning
confidence: 95%
“…The XPS of Ti2p, Si2p, B1s and C1s core-level spectra for the same samples is shown in Fig. 8 [45,46] at 456.4 and 462.4 eV correspond to TiC, [47,48] but the peaks may be also identified at 462.4 eV because of Ti 4+ 2p 3/2 from TiO 2 , [49] again another remaining one peak at 454.3 and 460.2 eV correspond to TiB 2 (Fig. 8a).…”
Section: Microstructure and Mechanical Properties Of Ti-si-b-c-n Filmsmentioning
confidence: 99%